Local Wisdom in Smart City Development Policy: Case Study of Makassar’s Sombere Smart City - Muh Alfian; Subando Agus Margono (Magister Administrasi Publik, 2023)
The city of Makassar is an example of smart city development practice and considered successful in emerging with a new policy innovation. The city was able to build a smart city not only based on information technology (IT) but also involves a local wisdom called “sombere”. The value of sombere in the life of the people of Makassar is a manifestation of the attitudes and behaviors that includes friendliness, kindness, and care. This study examines how the application of sombere local wisdom in supporting smart city-based policy in Makassar. This study uses qualitative methods with case study designs. Data collection is carried out through interviews, observations, and documentation, and were analyzed using an interactive model. The results showed that the value of friendliness, kindness, and care in sombere is the key to a successful implementation of smart city policies. Sombere could maintain the policy so that it remained sustainable and easily accepted by the people of Makassar. Local wisdom significantly has a positive effect on each service and program created. However, in some of the programs, local wisdom is difficult and even too forced to combine with the smart city program. The dimensions that are well supported by local wisdom are found in the dimensions of smart governance, smart living, and smart society. Meanwhile, the dimensions of the smart environment and smart economy are difficult to combine local values with the use of technology. Moreover, the value of local wisdom seems to be just a slogan in smart branding.